Interleukin 10 (IL-10) influences autoimmune response in primary Sjögren's syndrome and is linked to IL-10 gene polymorphism (2002)
Objective. To investigate the association between serum levels of interleukin 10 (IL-10), the synthesis of autoantibodies, salivary gland disease activity, clinical manifestations, and IL-10 microsatellite polymorphism in patients with primary Sjögren’s syndrome (pSS). Methods. Serum IL-10 and autoantibody levels [IgG anti-Ro and anti-La, total and IgA rheumatoid factor (RF)] were measured by ELISA. A minor salivary gland (MSG) biopsy was performed in all patients and the focus score was determined as a measure of salivary gland disease activity. In addition, IL-10 microsatellite typing was performed by polymerase chain reaction technique. Results. IL-10 concentration was higher in patients (n = 39) than in controls (n = 15) (21.4 ± 6.7 vs 2.5 ± 3.5 pg/ml; p = 0.001). We found a significant positive correlation between IL-10 levels and titers of IgA RF, anti-Ro, and anti-La antibodies, as well as focus score. In comparison with patients with low IL-10 production (< 9.5 pg/ml), patients producing high IL-10 had significantly more episodes of cutaneous vasculitis and a higher proportion of them carried the IL-10.G9 allele. Conclusion. Autoimmune response in pSS patients as well as salivary gland disease activity and cutaneous involvement appears to be mediated by IL-10 levels; in turn, there is a linkage with IL-10 gene polymorphism. (J Rheumatol 2002;29:1874–6).